1991
DOI: 10.3171/jns.1991.75.4.0564
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced meningiomas: experience at the Mount Sinai Hospital and review of the literature

Abstract: From the records of The Mount Sinai Hospital, seven cases which met established criteria for radiation-induced meningiomas were identified. This represents the largest series of radiogenic meningiomas documented in North America and includes both intracranial and intraspinal tumors. The records and pathological specimens were reviewed and these data analyzed with other cases retrieved from the world literature. This study reveals that radiation-induced meningiomas can be categorized into three groups based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
148
2
10

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(164 citation statements)
references
References 76 publications
4
148
2
10
Order By: Relevance
“…Neurological tissue was long considered relatively resistant to damage from x-rays, 16,24,45 and some authors suggested that higher doses allowed longer survival in patients with glioblastoma multiforme. 6,61 In 1938, Davidoff et al 13 described the clinical and histological effects of delivering 10-50 Gy in a single exposure, or 48-72 Gy in 2 fractions, applied directly to the brains and spinal cords in monkeys.…”
mentioning
confidence: 99%
“…Neurological tissue was long considered relatively resistant to damage from x-rays, 16,24,45 and some authors suggested that higher doses allowed longer survival in patients with glioblastoma multiforme. 6,61 In 1938, Davidoff et al 13 described the clinical and histological effects of delivering 10-50 Gy in a single exposure, or 48-72 Gy in 2 fractions, applied directly to the brains and spinal cords in monkeys.…”
mentioning
confidence: 99%
“…Although several studies support the role of previous radiation exposure in the development of brain tumors, most of them do not specifically mention PAs. 10,[15][16][17][18][19][20][21] This also holds true for the Israeli Tinea Capitis Study, in which comparisons between the rate of tumors in the irradiated group and the nonirradiated control group showed a significant excess risk for various tumors arising in the irradiated area, including benign and malignant brain tumors. 20 However, to date, an excessive risk for PA has not been indicated.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors may also have been induced by the radiotherapy as they have been described in other diseases treated by radiotherapy. 5,6 In fact, one of these patients received brain irradiation before allogeneic BMT and both received total body irradiation as part of their conditioning regimen. It is, however, clear that the role of radiotherapy in the genesis of these tumors can only be properly assessed by long-term follow-up trials comparing patients randomly assigned to be given CNS radiotherapy or no radiation.…”
Section: Discussionmentioning
confidence: 99%